Answered

Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Simplify the following algebraic expressions.
A) -2x + 5 + 10x - 9
B) 3(x + 7) + 2(-x + 4) + 5x


Sagot :

Answer:

A) 8x - 4   ||   B) 6x + 29

Step-by-step explanation:

A) -2x + 5 + 10x - 9

→ -2x+10x+5-9

→ -2x+10x-4

→ 8x - 4

B) 3(x + 7) + 2(-x + 4) + 5x

→ 3x + 21 - 2x + 8 + 5x

→ 6x + 29

Answer:

A) 8x - 4

B) 6x + 29

Step-by-step explanation:

A) -2x + 5 + 10x - 9 : given

= (10x - 2x) + (5 - 9) : put like terms together

= 8x - 4 : group

B) 3(x + 7) + 2(-x + 4) + 5x : given

= 3x + 21 - 2x + 8 + 5x : expand

= (3x - 2x + 5x) + (21 + 8) : put like terms together

= 6x + 29 : group

Thanks! Have a great day studying!

Answered by : ms115

We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.